Cell-specific STORM superresolution imaging reveals nanoscale organization of cannabinoid signaling - Dudok, Barna (Nat Neurosci, 2014)
A major challenge in neuroscience is to determine the nanoscale position and quantity of signaling molecules in a cell-type-, and subcellular compartment-specific manner. We therefore developed a novel approach combining cell-specific physiological and anatomical characterization with superresolution imaging, and studied the molecular and structural parameters shaping the physiological properties of synaptic endocannabinoid signaling in the mouse hippocampus. We found that axon terminals of perisomatically-projecting GABAergic interneurons possess increased CB(1) receptor number, active-zone complexity, and receptor/effector ratio compared to dendritically-projecting interneurons, in agreement with higher efficiency of cannabinoid signaling at somatic versus dendritic synapses. Furthermore, chronic Δ(9)-tetrahydrocannabinol administration, which reduces cannabinoid efficacy on GABA release, evoked dramatic CB(1)-downregulation in a dose-dependent manner. Full receptor recovery required several weeks after cessation of Δ(9)-tetrahydrocannabinol treatment. These findings demonstrate that cell-type-specific nanoscale analysis of endogenous protein distribution is possible in brain circuits, and identify novel molecular properties controlling endocannabinoid signaling and cannabis-induced cognitive dysfunction.